Kompetensi Karyawan Dan Efektivitas Penggunaan Video Conference Berbasis Skype Terhadap Efisiensi Waktu Perekrutan Karyawan - Hendi Sama (Computer Based Information System Journal, 2014)
The long term goal of this research is benefiting company in Kepulauan Riau Province regarding effectiveness of skype as technological bases and employee competencies in doing their job. This research attempts to examine how Skype and Competence of Employees affect Effectiveness of recruitment process. This research uses 2 independent variables and 1 dependent variable. The impact of independent variable was analyzed by regression model. Results show that there are significant interrelated dependence relationships among variables.